2013
DOI: 10.1016/j.rbp.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Is Positive Affect in Pregnancy Protective of Postpartum Depression?

Abstract: In pregnancy, negative affect was a predictor of postpartum depression, whereas positive affect showed a protective role. Future studies are required to explore whether psychotherapeutic strategies focusing on decreasing negative affect and enhancing positive affect in the last trimester of pregnancy can reduce the risk of postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 30 publications
2
21
0
7
Order By: Relevance
“…In an analysis of a cohort of 140 youngsters followed up over a period of 7 years, attenuated positive affect (rather than excessive negative affect) was indeed shown to be an early vulnerability factor for eventual unipolar depressive disorder in at-risk children (Olino et al, 2011). Furthermore, a cross-sectional observational study of 3-year-olds and older children reported that at-risk youngsters display lower levels of positive emotions but similar levels of negative emotions compared with their peers (Dietz et al, 2008;Shaw et al, 2006), while positive affect in late pregnancy significantly decreased the likelihood of experiencing postpartum depression by twofold (Bos et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…In an analysis of a cohort of 140 youngsters followed up over a period of 7 years, attenuated positive affect (rather than excessive negative affect) was indeed shown to be an early vulnerability factor for eventual unipolar depressive disorder in at-risk children (Olino et al, 2011). Furthermore, a cross-sectional observational study of 3-year-olds and older children reported that at-risk youngsters display lower levels of positive emotions but similar levels of negative emotions compared with their peers (Dietz et al, 2008;Shaw et al, 2006), while positive affect in late pregnancy significantly decreased the likelihood of experiencing postpartum depression by twofold (Bos et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…No entato, é importante termos em vista que, para além de uma percepção distorcida com relação às suas possíveis figuras de apoio, estudos indicam que a depressão pós-parto pode estar associada, entre outros fatores, à uma rede de GB Frizzo, LWF Martins, EX Lima e Silva, CA Piccinini, & AMP Diehl apoio social e familiar insuficiente (Arrais et al, 2014;Bos et al, 2013). Também devemos considerar que a Constelação da maternidade é composta por quatro temas inteligados, então é plausível pensar que uma boa percepção sobre a matriz de apoio pode influenciar para que a mãe tenha um bom desempenho nos demais temas, como o Tema vidacrescimento, o Tema do relacionar-se primário e o Tema da Reorganização da identidade.…”
Section: O Pai E Outras Figuras Masculinas De Apoiounclassified
“…A literatura enfoca a relevância das figuras de apoio no contexto da maternidade no período pré-natal e pós-natal (Frizzo, Kahl, & Oliveira, 2005;Levandowski, Barth, Munhós, Rödde, & Wendland, 2012). A existência dessa rede de apoio também se evidencia como fator protetor para sintomatologia depressiva (Arrais, Mourão, & Fragalle, 2014;Baptista, Baptista, & Torres, 2006;Bos, et al, 2013;Fonseca, Silva, & Otta, 2010;Frizzo & Piccinini, 2005;Goodman, 2004;Kim, Connolly, & Tamim, 2014;Nunes & Phipps, 2013;Prochnow & Lopes, 2007;Thiengo, Santos, Mason, Abelha, & Lovisi, 2011). Stern (1997) já ressaltava a importância da matriz de apoio frente a essa nova organização psíquica que surge com o ser mãe, a Constelação da maternidade.…”
unclassified
“…Na revisão de literatura que foi a base para a presente investigação, observou-se que esses fatores têm sido amplamente discutidos na literatura mundial, normalmente agrupados em três categorias: A) Fatores de risco e proteção psicossociais; B) Fatores de risco e proteção sociodemográficos/contextual; e C) Fatores de risco e proteção físicos e suas respectivas subcategorias, apresentadas a seguir: A.1) Fatores de risco psicológico/psiquiátrico: Ter histórico de episódios depressivos pessoais anteriores à gestação (Castro, Place, Billings, Rivera, Frongillo, 2015;Davey, Tough, Adair, & Bezies, 2011;El-Hachem et al, 2014;Figueira et al, 2011;Martín-Santos et al, 2012;Morais et al, 2015;Nunes, & Phipps, 2013;Rodríguez, Pineda, Álvarez, & Rojas, 2013;Rojas et al, 2010;Rohitkumar et al, 2014;Silva et al, 2012;Tian Tian et al, 2012;Urdaneta et al, 2011); Presença de estresse na gestação (Bos et al, 2013;Figueira et al, 2011;Lara, Navarro, Navarrete, & Yle, 2010;Liu, & Tronick, 2013;Martín-Santos et al, 2012;Nunes, & Phipps, 2013;Rodrigues, & Schiavo, 2011;Silva et al, 2012;Tian Tian et al, 2012); Ansiedade gestacional (Davey et al, 2011;Figueira et al, 2011;Garfield et al, 2015;Lara et al, 2010;Rogers, Kidokoro, Wallendorf, & Inder, 2013); Depressão gestacional (Faisal-Cury, & Menezes, 2012;McMahon et al, 2015;Nunes, & Phipps, 2013;Turkcapar et al, 2015); História de DPP anterior (Faisal-Cury, & Menezes, 2012;Kinsey, Baptiste-Roberts, Zhu, &...…”
Section: Fatores De Risco E Proteção Associados à Depressão Pós-partounclassified